1994
DOI: 10.1016/0014-5793(94)80389-7
|View full text |Cite
|
Sign up to set email alerts
|

α2A‐Adrenergic receptors activate protein kinase C in human platelets via a pertussis toxin‐sensitive G‐protein

Abstract: Abstract4,4'-Diisothiocyanato-stilbene-2,2'-dlsulfonic acid (DIDS) stimulates human platelets via cc ,,-adrenerglc receptor-mediated activation of protein kmase C (PKC) independent of the phospholipase C pathway. Here we show, that in permeabilized platelets activation of PKC by DIDS (20 PM), measured as "P incorporation in pleckstrin, is completely inhibited by guanosine 5'-(2-0-thio)diphosphate (200 fiM), an inhibitor of heterotrimeric G-proteins. Also pertussin toxin (4 ,&ml), which ADP-ribosylates the a-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Indeed, Erk1/2 phosphorylation may be mediated by either Gq or Gi/o and be dependent on PKC or Ras activation 2040 As α 2 adrenoceptors stimulate PKC via a Gi dependent pathway in OK cells or in human platelets,41 42 and as they increase phospholipase C activity and intracellular Ca ++ in HEL or transfected CHO cells,43 we investigated if the effect of UK14304 involved PKC activation. Short term exposure of Caco2-3B cells to the PKC activator PMA resulted in an increase in Erk phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Erk1/2 phosphorylation may be mediated by either Gq or Gi/o and be dependent on PKC or Ras activation 2040 As α 2 adrenoceptors stimulate PKC via a Gi dependent pathway in OK cells or in human platelets,41 42 and as they increase phospholipase C activity and intracellular Ca ++ in HEL or transfected CHO cells,43 we investigated if the effect of UK14304 involved PKC activation. Short term exposure of Caco2-3B cells to the PKC activator PMA resulted in an increase in Erk phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to investigate the effects of cAMP enhancing drugs on platelet aggregation, in experimental conditions that provide the concomitant activation of G i and G q , and to assess whether the inhibitory action is exerted directly at the level of ␣IIb␤3 and not merely due to the lack of ADP release. For this purpose we studied the effects of high concentrations of iloprost on platelet aggregation and fibrinogen binding evoked by the simultaneous activation of G q (by means of U46619) and G i (by means of epinephrine) (16) proteins. In a recent work we have shown that the activation of an enzyme downstream of Gq, such as phospholipase C (PLC) or protein kinase C (PKC), was able to cause the conformational changes in the integrin ␣IIb␤3 provided a G i protein coupled receptor was activated (17).…”
mentioning
confidence: 99%
“…The most likely subtype of G protein mediating this effect is Gi as linkage between a2-adrenoceptors and this G protein has been described in other cell types (Limbird, 1988;Nieuwland et al, 1994). However, the possibility that the action of a2-adrenoceptors is mediated by some other pertussis toxinsensitive G protein cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%